2013
DOI: 10.5551/jat.18333
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, Design, and Baseline Characteristics of a Trial for the Prevention of Diabetic Atherosclerosis Using a DPP-4 Inhibitor: The Study of Preventive Effects of Alogliptin on Diabetic Atherosclerosis (SPEAD-A)

Abstract: Aim: Alogliptin, an efficacious inhibitor of DPP-4 that improves glycemic control, as well as the pancreatic beta-cell function, is now increasingly used to accomplish glycemic targets in type 2 diabetic patients. Interestingly, recent experimental studies have shown that alogliptin exerts anti-atherosclerotic effects in GLP-1-dependent and -independent manners. The aim of the present ongoing study is to investigate the preventive effects of alogliptin on the progression of atherosclerosis in type 2 diabetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The Study of Preventive Effects of Alogliptin on Diabetic Atherosclerosis (SPEAD-A) trial was a multicenter prospective, randomized, open-label, blinded-end point (PROBE) study, as described previously (20). This study was registered on the University Hospital Medical Information Network Clinical Trials Registry (UMIN000005311), a nonprofit organization in Japan that meets the requirements of the International Committee of Medical Journal Editors (ICMJE).…”
Section: Methodsmentioning
confidence: 99%
“…The Study of Preventive Effects of Alogliptin on Diabetic Atherosclerosis (SPEAD-A) trial was a multicenter prospective, randomized, open-label, blinded-end point (PROBE) study, as described previously (20). This study was registered on the University Hospital Medical Information Network Clinical Trials Registry (UMIN000005311), a nonprofit organization in Japan that meets the requirements of the International Committee of Medical Journal Editors (ICMJE).…”
Section: Methodsmentioning
confidence: 99%
“…Alogliptin is prescribed to be combined with metformin even though they have different mechanisms of action in improving glucose metabolism [ 17 ]. Moreover, alogliptin can reduce inflammation and thereby perform anti-atherosclerotic effects by inhibiting the monocyte activation/chemotaxis [ 19 ]; it prevents migration of monocytes and actin polymerization via Rac-dependent mechanism [ 20 ], and can act by inhibiting the inflammation in diabetic apoE-deficient in animals [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Alogliptin, a DDP-4 inhibitor has advantage over other antidiabetic agents as it does not produce weight gain [ 66 ], and its ability to inhibit atherosclerosis and inflammation [ 19 ]. Alogliptin helps to improve glycemic control in adults with T2DM together with diet and exercise plan [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonographic scans of the carotid artery are performed by expert sonographers who are specifically trained to perform the prescribed study examination, as reported previously [36]. To avoid inter-sonographer variability, each participant is examined by the same sonographer with the same equipment (high-resolution B-mode ultrasound scanner equipped with a high frequency (>7.5-MHz) linear transducer, with a limit of detection of <0.1 mm) throughout all the visits.…”
Section: Methods and Designmentioning
confidence: 99%